2020
DOI: 10.3390/children7120252
|View full text |Cite
|
Sign up to set email alerts
|

Management of Molar Incisor Hypomineralisation (MIH): A 1-Year Retrospective Study in a Specialist Secondary Care Centre in the UK

Abstract: (1) Background: Molar incisor hypomineralisation (MIH) is an enamel defect that affects an estimated 14.2% of children worldwide. Care takes place in primary and secondary care facilities. (2) Aim: To investigate how children with MIH are managed within a specialist centre in the north of England. (3) Method: A retrospective service evaluation within the paediatric dentistry department was registered with the clinical governance unit. Children who attended consultant-led new-patient clinics between 1 January a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The decision on the choice of treatment must be made individually, taking into account the severity of the lesions, the symptomatology of the affected tooth, the age, and the aesthetic expectations of the patient [ 43 ]. The therapy must therefore include prevention, recovery, immediate treatment, and long-term planning; the following points are of particular importance in the prophylaxis program for low mineralized areas: regular professional oral hygiene, use of fluoride preparations (topical fluoride prophylaxis or three/four applications of sodium fluoride or fluoride varnish), and the use of CPP-ACP products and sealings [ 44 , 45 ]; it is also useful to use biomimetic nano-hydroxyapatite for the reduction of enamel hypomineralization. This has the greatest effectiveness if applied daily for a minimum of 2–3 min up to a maximum of 10 min for 10 days a month [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decision on the choice of treatment must be made individually, taking into account the severity of the lesions, the symptomatology of the affected tooth, the age, and the aesthetic expectations of the patient [ 43 ]. The therapy must therefore include prevention, recovery, immediate treatment, and long-term planning; the following points are of particular importance in the prophylaxis program for low mineralized areas: regular professional oral hygiene, use of fluoride preparations (topical fluoride prophylaxis or three/four applications of sodium fluoride or fluoride varnish), and the use of CPP-ACP products and sealings [ 44 , 45 ]; it is also useful to use biomimetic nano-hydroxyapatite for the reduction of enamel hypomineralization. This has the greatest effectiveness if applied daily for a minimum of 2–3 min up to a maximum of 10 min for 10 days a month [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In extraction cases, 127 were sampled in Phase I (69 used GA as a method of pain control during the extraction, 4 used inhalation sedation, and only one used LA alone), whereas 117 were sampled in Phase II (GA was used as a method of pain control). Regarding the number of cFPMs extracted per patient, 59.7% of children (120/201) had all FPMs removed, 8.5% (17) had three FPMs removed, 22.9% (46) had extraction of two FPMs, and 8.9% (18) had extraction of only one FPM.…”
Section: Resultsmentioning
confidence: 99%
“…Humphreys and Albadri (2020) investigated the management of molar-incisor hypomineralisation (MIH)-affected teeth in children and found that of the 48 sampled children, 25 (52.1%) patients had extraction of at least one MIH-affected FPM. 46 Taylor et al (2019) used clinical vignettes to investigate the management of the poor prognosis of FPMs by GDPs and specialists in paediatric dentistry. They revealed that GDPs would prefer to restore cFPMs in comparison with specialists, who were more likely to extract such teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that MIH-affected patients often benefit from multidisciplinary input (Elhussein and Jamal, 2020; Humphreys and Albadri, 2020; Lygidakis et al, 2010; Office of the Chief Dental Officer England, 2018), it was important to explore current MDT care provision. Approximately half of the respondents in both groups agreed that these patients should be managed through an MDT-type clinic.…”
Section: Discussionmentioning
confidence: 99%